Heterosis in Intra- and Interspecific Diallel Crosses Among Some Cotton Cultivars of Sudan - C. Misaka, Beatrice; M. Ali, Abdelbagi; S. Ibrahim, Abu Elhassan (المجلة الزراعية, 2021)
Estimates of mid-parent heterosis for seed cotton yield and its components were studied in six intra- hirsutum , six intra-barbadense and sixteen interspecific ( Gossypium hirsutum x Gossypium barbadense) hybrids. The material was grown in 2000 and 2001 seasons at the Gezira Research Station, Wad Medani, Sudan. Highly significant variability was detected for all the measured traits. Two interspecific hybrids, Acala(93)H x B-Pima and Acala(93)H x Barakat-S, outyielded the best parent by 127.6% and 111.6%, and 116.2% and 114.4% in both seasons, respectively. The magnitude of heterotic effect was greater in the interspecific hybrids than in the intraspecific hybrids. Maximum heterosis for seed cotton yield, number of sympodia and bolls per plant and fiber quality properties was obtained in six interspecific hybrids, viz. Acala (93)H x B-Pima, Acala (93) H x Barakat-90,  Acala (93) H x Barakat- S, Shambat-B x B-Pima,  Albar(57)12 x Barakat-90 and Scala(93)H x Huda. This suggested that these hybrids can be used as commercial hybrids, hybrid performing doubled haploids and as source populations for further selection to improve cotton yield.